Multiple anthelmintic resistance in gastrointestinal nematodes of small ruminants in Bangladesh. (August 2020) - Dey, Anita Rani; Begum, Nurjahan; Anisuzzaman,; Alim, Md. Abdul; Alam, Mohammad Zahangir
Abstract: Anthelmintic resistance (AR) against gastrointestinal nematodes (GINs) of sheep and goats is a global concern. To address the problem, this study assessed the status of AR in different government and private sheep and goat farms in Bangladesh. We conducted fecal egg count reduction test (FECRT) and Egg hatch assay (EHA) experiments. For the detection of resistant larvae, pooled fecal samples from treated and non-treated groups were subjected to coproculture. Furthermore, 195 adult Haemonchus parasites were genotyped to ascertain benzimidazole (BZ) resistance allele from seven topographic zones of Bangladesh using allele specific PCR (AS-PCR). In FECRT, the percentage reduction along with 95% confidence intervals indicated that GINs were resistant to albendazole (ABZ), levamisole (LEV) and ivermectin (IVM). Coproculture revealed that Haemonchus spp., Oesophagostomum spp. and Trichostrongylus spp. were resistant to anthelmintics. ABZ resistance was also confirmed by in vitro EHA in all the farms except the private goat farm in Mymensingh. The genotype frequencies were 6% for homozygous resistant (rr), 59% for heterozygous (rS) and 35% for homozygous susceptible (SS) among different topographic zones. The allelic frequency of the mutation conferring resistance (r) ranged from 25% to 47% signifying resistance to BZ in nematodes of sheep/goats. The genotype frequencies (rr, rS and SS) and allelic frequencies (r and S) varied significantly (p˂0.05) in different zones in Bangladesh. Overall, the data suggest an alarming condition created by multiple AR in Bangladesh. Graphical abstract: Unlabelled Image Highlights: Multiple anthelmintic resistance was detected in gastro-intestinal nematodes. Haemonchus, Oesophagostomum and Trichostrongylus were resistant in different farms. Resistance was detected against albendazole, levamisole and ivermectin. Benzimidazole resistance was confirmed by Allele Specific-PCR. The resistant allelic frequency (r) against benzimidazole ranged from 25%–47%.